ChemInform Abstract: Hydrophobically Directed, Catalyst‐Free, Multi‐Component Synthesis of Functionalized 3, 4‐Dihydroquinazolin‐2(1H)‐ones. Issue 28 (June 2016) - Ramana, Daggupati V.; Vinayak, B.; Dileepkumar, V.; Murty, U. S. N.; Chowhan, L. Raju; Chandrasekharam, M.
Abstract: A wide range of the title quinazolinones (44 examples) is prepared by environmentally benign one‐pot, three‐component reaction of o‐formyl carbamate, a primary amine, and indole or naphthol as nucleophiles involving a Mannich type reaction and subsequent intramolecular cyclization.